Potential therapeutic application of mesenchymal stem cell-derived exosomes in SARS-CoV-2 pneumonia - Akbari, Ali (Stem Cell Res Ther, 2020)
BACKGROUND: The outbreak of a new virus known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has now become the main health concern all over the world. Since effective antiviral treatments have not been developed until now, SARS-CoV-2 is severely affecting countries and territories around the world. METHODS: At the present review, articles in PubMed were searched with the following terms: mesenchymal stem cells, exosomes, coronavirus, and SARS-CoV-2, either alone or in a combination form. The most relevant selected functions were mesenchymal stem cell-derived exosomes and SARS-CoV-2 virus infection. RESULTS: SARS-CoV-2 could damage pulmonary cells and induce secretion of different types of inflammatory cytokines. In the following, these cytokines trigger inflammation that damages the lungs and results in lethal acute respiratory distress syndrome (ARDS). The main characteristic of ARDS is the onset of inflammation in pulmonary, hyaline formation, pulmonary fibrosis, and edema. Mesenchymal stem cell-derived exosomes (MSC-Exo) are believed to have anti-inflammatory effects and immune-modulating capacity as well as the ability to induce tissue regeneration, suggesting a significant therapeutic opportunity that could be used to SARS-CoV-2 pneumonia treatment. Besides, exosomes may serve as a biomarker, drug delivery system, and vaccine for the management of the patient with SARS-CoV-2. CONCLUSION: MSC-Exo may serve as a promising tool in the treatment of SARS-CoV-2 pneumonia. However, further work needs to be carried out to confirm the efficacy of exosomes in the treatment of SARS-CoV-2 pneumonia.